2015
DOI: 10.18203/2319-2003.ijbcp20150010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic self-medication pattern among under-graduate medical students of Adichunchanagiri Institute of Medical Sciences, BG Nagar, Karnataka: a cross-sectional questionnaire-based study

Abstract: INTRODUCTIONIn the developing countries, 60-80% of health problems are due to self-medication 1 and the drugs are dispensed over the counter without medical supervision.2 There is an increase in the trend for self-care which resulted in self-medication with powerful drugs including drug combinations.3 People resort to self-medication since it's a lower cost alternative for people who cannot afford the cost of clinical service. Studies have revealed that the increase in self-medication was due to a number of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 9 publications
6
17
1
Order By: Relevance
“…In present study, the prevalence of self medication with analgesics was found to be 83.3% while in studies done by Badiger et al, Shivamurthy et al, Al Essa et al, found prevalence of analgesic self medication to be 92%, 63.6% and 73.2% respectively. 4,8,9 Present study thus supports earlier studies with similar results signifying increasing self medication practice among medical students.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In present study, the prevalence of self medication with analgesics was found to be 83.3% while in studies done by Badiger et al, Shivamurthy et al, Al Essa et al, found prevalence of analgesic self medication to be 92%, 63.6% and 73.2% respectively. 4,8,9 Present study thus supports earlier studies with similar results signifying increasing self medication practice among medical students.…”
Section: Discussionsupporting
confidence: 91%
“…The most common reason for self medication in our study was quick relief (73.3%) which is similar to study done by Gupta V et al, and prior experience of illness (38.3%) reported in present study was also reported from studies done in Zafar et al and Abay et al [11][12][13] Time saving was the reason for self medication with analgesics in the study done by Shivamurthy S et al which is different from present study. 8 In present study, most common source of drug information was from medical textbooks (61.6%) which is similar to studies done by Badiger et al and Abay SM et this study was also reported by Shivamurthy et al 8 The participants thus indulged in self medication practice owing to their self-assumed sufficient pharmacological knowledge.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, the prevalence of self-medication was 100% unlike other studies were the prevalence ranged from 57.1% to 92%. [9][10][11] In a study conducted by Abay et. al 55.6% of students agree with the concept of selfmedication whereas in the present study, 47.3% of the students agree.…”
Section: Discussionmentioning
confidence: 99%